2010
DOI: 10.1590/s1519-38292010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico da Síndrome de Turner: a experiência do Instituto Estadual de Diabetes e Endocrinologia - Rio de Janeiro, de 1970 a 2008

Abstract: O b j e c t i v e s : t o d e s c r i b e t h e R i o d e J a n e i ro St a t e Institute of Diabetes and Endocrinology's experience in diagnosing Turner Syndrome (TS), focusing on the distribution of chromosomes, age, and typical signs and symptoms, according to life stage (breast feeding, childhood, adolescence and adulthood). M e t h o d s : a d e s c r i p t i v e s t u d y w a s c o n d u c t e d o f 178 patients, attending the Institute between 1970 and 2 0 0 8 f o r t h e p u r p o s e s o f s t a t i s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
1
3
0
2
Order By: Relevance
“…Previous studies with Brazilian patients showed similar mean age at diagnosis compared to this series (10.9 years) (4,17,18).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies with Brazilian patients showed similar mean age at diagnosis compared to this series (10.9 years) (4,17,18).…”
Section: Discussionsupporting
confidence: 79%
“…TS is usually diagnosed with karyotype using GTG banding. About 50%-60% of the cases present with 45,X monosomy, 5%-10% show structural abnormalities and 30%-40% have mosaic cell lineages, including cells with structurally abnormal X and presence of Y chromosome (5%-10% of mosaic cases) (1)(2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Ainda, conforme exposto por Mandelli e Abramides (2012), alterações visuais, auditivas e específicas da cavidade oral estão presentes, dentre elas: estrabismo, nistagmo, ptose, epicanto, miopia, catarata, deficiência auditiva/ perda auditiva neurossensorial, lóbulo da orelha proeminente, otite média, má oclusão dentária, mandíbula pequena e palato ogival. Health Review, Curitiba, v.4, n.4, p. 16723-16730 jul./aug 2021 Outras manifestações importantes que podem ser apresentadas são o tórax alargado, hipertelorismo mamário, cubitus valgus e linfedema congênito (JUNG et al, 2010). Além disso, as pacientes com ST apresentam risco aumentado para alterações cardiovasculares (coartação da aorta, defeitos no septo ventricular) e renais (como duplicidade do sistema coletor, rotação dos rins), sobrepeso e obesidade, osteoporose, doenças tireoidianas (principalmente hipotireoidismo), hipertensão, resistência insulínica, hipercolesterolemia, endocardite e doenças autoimunes, entre elas a doença celíaca e o vitiligo (GUIMARÃES et al, 2001).…”
Section: Manifestações Clínicasunclassified
“…Curiosamente, o caso relacionado à hipotonia é oriundo de uma UTI Neonatal e revelou cariótipo compatível para síndrome de Turner (45,X[20]/46,XX[55]). Estudo de Jung et al (2010), envolvendo o diagnóstico para síndrome de Turner com 178 casos, revelou que apenas 11,3% das pacientes tiveram o diagnóstico de Turner na lactância, 25,3% na infância, 51,1% na adolescência e 12,4% na fase adulta. Ainda segundo o estudo de Jung et al (2010), a média de idade para o diagnóstico em casos mosaicismo foi de aproximadamente 13 anos.…”
Section: Artigo Originalunclassified